Efektifitas Penggunaan Media Video dan Buku Saku Terhadap Pengetahuan Mahasiswa Tentang Asfiksia dan Resusitasi Neonatus - Ry Eny Mian Marisi Br. Simanjuntak; Evrina Solvia Soleh (NHM PRESS, 2022)
Babies with asphyxia will be able to survive if they get the right treatment. In order to produce graduates who are skilled in asphyxia relief, it is necessary to develop learning media that attract students' interest in learning. This study aims to analyze the effectiveness of using pocket book media on neonatal resuscitation skills in the fourth semester of applied midwifery undergraduate students. This research is a quantitative research with a pilot study design with a comparative posttest only control design method. The sample in this study was the total population, namely 38 undergraduate students of applied midwifery in the fourth semester. Data analysis using Wilcoxon and Mann Withney test. The results showed that before being given Learning using Video Media, the mean value of student knowledge was 6.53, then after the intervention changed to 9.89, with a P-value <0.05. Before being given learning using pocket book media, the mean value was 6.68, then after the intervention the mean value became 9.95 with P-value <0.05. The results of the Mann Withney test obtained a P-value = 0.55. The conclusion of the study is that both learning media are effective in increasing students' knowledge of neonatal resuscitation in students of Health Polytechnic, Ministry of Health, Jambi, undergraduate program of applied midwifery in the fourth semester.